Pemanfaatan Teknik Web Scraping Untuk Estimasi Tarif dan Sarana Transportasi Bus Jakarta-Malang Pada Traveloka - Anjani, Dewi; Novianti, Desi; Bachtiar, Yogi (Journal of Informatics, Electrical and Electronics Engineering, 2025)
The development of land transportation technology in Indonesia has significantly affected people's mobility. In the context of the world of land transportation, data is a valuable asset that can provide deep insights into various aspects of land transportation, from travel route planning to traffic management. By utilizing data effectively, we can build a more efficient, safe, and sustainable transportation system. Data is an important component in supporting information. Nowadays, there is a lot of data on a website that can provide us with information and insight or views on an event. Information on a website is not only about one or two pieces of information but can also be a collection of data that is collected and requires further analysis. One way to collect data and information from a website is with web scraping techniques. Researchers want to apply this web scraping technique to analyze the estimation of fares and transportation facilities for the Jakarta-Malang bus. The goal is to find out the ideal fare and transportation advice as a support for a mature travel plan. The result If we want to travel from Jakarta to Malang using land transportation, there are 14 PO. Buses are available as options with various classes and departure times. Bus fares offered vary from Rp. 325,500 to Rp. 700,000.